(untitled) (Asian Journal of Medical and Biological Research, 2025)
Growing concerns over the use of antibiotics in poultry production have led to increased exploration of natural feed additives with health-promoting benefits. This study aimed to assess the impact of fenugreek seed (Trigonella foenum-graecum) supplementation in broiler diets as a potential substitute for antibiotic growth promoters. Conducted over a 28-day period (May 8 to June 5, 2019) at the Sher-e-Bangla Agricultural University Poultry Farm in Dhaka, the trial involved 150 Cobb 500 day-old broiler chicks. The birds were distributed randomly across five dietary groups, each with three replicates containing 10 chicks. The treatment groups included a control (no additive), an antibiotic-supplemented diet, and diets supplemented with fenugreek seed at 1%, 1.5%, and 2% inclusion levels. The findings revealed a significant (P<0.05) enhancement in final body weight and dressing percentage in birds fed fenugreek, with the 1.5% group achieving the highest body weight (1528.33 ± 57.47 g). Although feed conversion ratio (FCR) did not show significant variation across treatments, birds receiving the 1% fenugreek diet consumed the most feed (2289.67 ± 2.60 g). No significant differences (P>0.05) were observed in the relative weights of internal organs or immune tissues. Blood cholesterol levels significantly decreased in the fenugreek-fed groups, while glucose levels remained unchanged. Hematological profiles improved notably in treated birds, particularly in hemoglobin concentration, red and white blood cell counts, and lymphocyte percentages. Microbial analysis showed that fenugreek supplementation reduced pathogenic bacteria such as E. coli and Salmonella, while promoting beneficial Lactobacillus populations. Additionally, antibody titers against Newcastle disease were significantly higher (P<0.05) in fenugreek-treated groups. Incorporating fenugreek seed into broiler diets positively influenced growth metrics, enhanced immune function, improved gut microbial balance, and supported key hematological parameters. These outcomes highlight fenugreek seed as a promising natural alternative to synthetic antibiotics in broiler production systems. Asian J. Med. Biol. Res. 2025, 11(4), 73-87